The Determination of Morphine in the Larvae of Calliphora stygia using Flow Injection Analysis and HPLC with Chemiluminescence Detection - Gunn, J.; Shelley, C.; Lewis, Simon; Toop, T.; Archer, M. (Preston Publications Inc, 2006)
Selective determination of morphine in the larvae of Calliphora stygia (Fabricius) (Diptera: Calliphoridae) using acidic potassium permanganate chemiluminescence detection coupled with flow injection analysis and high-performance liquid chromatography (HPLC) is described. Larvae of C. stygia were reared on minced meat substrates that had been spiked with varying concentrations of morphine. Morphine concentrations were chosen to reflect typical levels in human tissues from opiate overdose victims. After maturing on substrates, larvae were analyzed for the presence of morphine using chemiluminescence detection coupled to flow injection analysis and a rapid HPLC method. Analysis of the larval matrix by flow injection analysis with chemiluminescence detection indicated the presence of interferants capable of generating chemiluminescence. A rapid chromatographic separation with a monolithic column allowed selective determination of morphine in larvae using postcolumn chemiluminescence detection. Larvae of C. stygia reared on substrates containing morphine at concentrations of 500 and 1000 ng/g did not sequester morphine at detectable concentrations. Larvae reared on substrates containing morphine concentrations of 2500, 5000, and 10,000 ng/g tested positive for the drug at concentrations of 765, 2720, and 3010 ng/g, respectively.